The future of the European law of civil procedure : coordination or harmonisation? / edited by Fernando Gascón Inchausti, Burkhard Hess. - Gascón Inchausti, Fernando; Hess, Burkhard (Intersentia, 2020)
The European lawmaker is currently overseeing what appears to be a paradigm shift in the way that cross-border litigation is conducted within the European Union. This matter was initially conceptualised from the perspective of international judicial cooperation, based on the notion of mutual trust and mutual recognition. Recent developments, however, have introduced the option of harmonisation as a new regulatory approach. The first part of the book is focused on the possible methodological approaches at hand. Special emphasis is placed on the role of the Court of Justice of the European Union as a promoter of a European Procedural Law (principle of effectiveness and principle of equivalence). The second part assesses to what extend harmonisation is already used: vertically, through the regulations on international judicial cooperation, for example the European Account Preservation Order; and horizontally, through the promotion of harmonised standards promoted by the directives on intellectual property rights and competition damages (access to information and evidence), or in the directive on trade secrets and in the field of data protection (protection of confidential information). With a view to the future, the final part examines two more recent initiatives: ELI-UNIDROIT and the proposal for a directive on common minimum standards of civil procedure in the EU. The Future of the European Law of Civil Procedure: Coordination or Harmonisation? clearly outlines the motivations of the various national and institutional players in the regulation of civil procedural law and identifies potential obstacles likely to be encountered along the way that will be useful for every lawyer in the field. Fernando Gascón Inchausti is Full Professor of Procedural Law at the Complutense University of Madrid, Spain. He is currently Executive Secretary General of the International Association of Procedural Law and General Assistant Editor of the International Journal of Procedural Law. BURKHARD HESS is Professor of Law and Founding and Executive Director of the Max Planck Institute Luxembourg for International, European and Regulatory Procedural Law. He is President of the ILA Committee on the Protection of Privacy in Private International and Procedural Law."